Plasma cell gingivitis: A case report - Aravinda Konidena; Gagan Puri; Deepa Jatti; Simarjeev Singh (Wolters Kluwer Medknow Publications, 2014)
Plasma cell gingivitis (PCG) is a rare condition of the gingiva, characterized by infiltration of plasma cells. The etiology is largely unknown, but it is thought to be due to a hypersensitivity reaction to an allergen. We report an interesting case of plasma cell gingivitis in a 28-year-old male patient, suffering from muscular dystrophy type II, diagnosed by histopathological examination of the excised gingival tissue, which was necessitated due to the refractory nature of the lesion to conventional treatment. The patient responded to topical 0.1% triamcinolone acetonide and 5 mg Levocetirizine.